Are platform workers willing to unionize? Exploring survey evidence from 14 European countries - Kurt Vandaele; Agnieszka Piasna; Wouter Zwysen (International Labour Organization (ILO), 2024)
Embedded in the particular model of work organization of digital labour platforms, platform workers face several hurdles discouraging them from becoming trade union members. These relate to algorithmic management, regulatory arbitrage regarding the employment arrangements and the promotion of an entrepreneurial orientation among platform workers. Nevertheless, based on data from a representative survey in 14 European countries, union density in the platform economy stands at 13.4 per cent. This should be interpreted as a kind of "platform unionism" that exists by coincidence, however, as union membership is most likely rooted in the labour market status of platform workers in the conventional economy. Compared to the general population, platform workers have stronger pro-union attitudes and are more receptive to union membership. Probably partly reflecting difficulties in the ability to unionize, there is still a gap, though, between attitudes and willingness to unionize: whereas about two-thirds of platform workers hold positive attitudes towards unions, only over a quarter state that they would like to join a union. Apart from those positive pro-union attitudes, the propensity to unionize also seems to be determined by engagement in offline networks that promote a social norm of union membership and online participation in digital work-related communities. While these findings could inform union recruitment and organizing strategies, it is needless to say that the heterogeneity of the platform workforce, strongly influenced by the different ways in which workers participate in the platform economy, requires at the same time tailor-made strategies.
Keywords: 330; non-standard forms of employment; digital labour; workers; gig economy